Assessment of yield and postharvest traits of three strawberry (Fragaria × ananassa Duch.) cultivars grown at farmer’s field in Rawalakot, Azad Jammu and Kashmir - Zulfiqar, Asim; Maqbool, Mehdi; Zahid, Noosheen; Khaliq, Abdul; Hassan, Imran; Ali, Asgar; Singh, Ajit; Khan, Muhammad Riaz (Journal of Pure and Applied Agriculture, 2025)
Strawberry (Fragaria × ananassa Duch.) is highly palatable berry fruit. It is a rich source of vitamins and minerals with fabulous flavour and tantalizing aroma. While previous research trials at departmental level demonstrated successful strawberry cultivation in Rawalakot, cultivar specific performance under open-field conditions at farmer’s field has not been assessed. Therefore, the present study was conducted to evaluate the performance of three strawberry cultivars (Chandler, Seascape, Tribute) under open-field conditions. Runners of each cultivar were planted, and data were collected on vegetative growth, flowering, fruit yield, and postharvest attributes. The experimental arrangements were made in a randomized complete block design (RCBD) with three replications, and data analysis was performed using ANOVA in Statistix 8.1, with mean comparisons via LSD (P ≤ 0.05). Results indicated that Chandler exhibited higher vegetative growth, with the highest survival rate (97%), number of runners (4.96), leaf area (42.63 cm²), and chlorophyll content (43.23 g/ml). It also produced the highest number of flowers (14.32), fruits per plant (10.32), and fruit yield (118.32 g/plant). Chandler also excelled in postharvest quality, showing the highest total soluble solids (7.56%), vitamin C (21.34 mg/100 g), total anthocyanins (4.02 mg/100 g FW), and antioxidant activity (102.12 µg/100 mg FW). Tribute required the longest duration for flowering (51.34 days) and harvesting (92.56 days). Overall, Chandler was the most promising cultivar for superior yield and postharvest quality in Rawalakot’s open-field conditions. Moreover, the study highlights the potential future benefits for local farmers through the cultivation of strawberries.